2021
DOI: 10.3892/etm.2021.10705
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of growth differentiation factor‑15 in brain disorders (Review)

Abstract: Brain disorders, such as Alzheimer's and Parkinson's disease and cerebral stroke, are an important contributor to mortality and disability worldwide, where their pathogenesis is currently a topic of intense research. The mechanisms underlying the development of brain disorders are complex and vary widely, including aberrant protein aggregation, ischemic cell necrosis and neuronal dysfunction. Previous studies have found that the expression and function of growth differentiation factor-15 (GDF15) is closely ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 120 publications
(158 reference statements)
0
10
0
Order By: Relevance
“…It has been reported to play an important role in regulating apoptosis, inflammation, angiogenesis, and lipid metabolism, etc. in various debilitating conditions, including PD, Alzheimer's disease, Huntington's disease, and stroke [35,36]. Exogenous GDF-15 could rescue 6-OHDA-induced apoptosis of DAergic neurons both in vitro and in vivo [34].…”
Section: Menscs Secreted Multiple Molecules Playing Neuroregulatory R...mentioning
confidence: 99%
“…It has been reported to play an important role in regulating apoptosis, inflammation, angiogenesis, and lipid metabolism, etc. in various debilitating conditions, including PD, Alzheimer's disease, Huntington's disease, and stroke [35,36]. Exogenous GDF-15 could rescue 6-OHDA-induced apoptosis of DAergic neurons both in vitro and in vivo [34].…”
Section: Menscs Secreted Multiple Molecules Playing Neuroregulatory R...mentioning
confidence: 99%
“…Recent studies found that the p53 protein participates in the pathogenesis of podocyte apoptosis (Choy Liang et al, 2021;Yang et al, 2021). As a tumor suppressor, p53 could safeguard the genome and prevent malignant transformation by halting the cell cycle and promoting apoptosis (Jiang et al, 2021;Thoms and Stark, 2021). p53 is increased under stimulation, and then upregulates the expression of pro-apoptotic genes (Eliaš and Macnamara, 2021).…”
Section: P53 Pathwaysmentioning
confidence: 99%
“…Given the anomalous scenario whereby a small subset of neurons restricted to one region of the brainstem is driving such profound effects on body weight regulation and nausea/emesis elicited by a host of disease-driven elevations in GDF15 signaling, there is an urgent need to better understand the phenotype of these neurons. As GDF15 signaling becomes increasingly linked to the progression of diseases, including cancer, obesity, cachexia, uncontrolled nausea/vomiting, and cardiovascular disease [ [22] , [23] , [24] , [25] ], understanding the transcriptomic changes elicited by GDF15 in not only GFRAL and RET-coexpressing neurons, but also the second order transcriptome alterations in other cells in the AP and NTS is imperative for the development of future therapeutics.…”
Section: Introductionmentioning
confidence: 99%